ON THE INDUCTIVE PROOF OF LEGENDRE ADDITION THEOREM - Malecek K.; Nadenik Z. (My University, 2001)
Various proofs of the Legendre Addition Theorem, as they appear in the mathematical literature, are outlined. The proof of the mentioned theorem, based on the induction method, is analyzed in detail.
Keywords: LEGENDRE POLYNOMIALS; LEGENDRE ASSOCIATED FUNCTIONS; LEGENDRE ADDITION THEOREM; HISTORY; METHODICS